Comparing the efficacy of different types of exercise for the treatment and prevention of depression in youths: a systematic review and network meta-analysis - Zhang, Yihan; Li, Geng; Liu, Chengzhen; Guan, Jinliang; Zhang, Yuantong; Shi, Zifu (Frontiers in Psychiatry, 2023)
Purpose: Depression disorder is the most commonly diagnosed type of mental health disease among youths. Although a plethora of evidence suggests a positive relationship between exercise and lower levels of depression in youths. The findings on the magnitude variation of this relationship are inconclusive with respect to the preventive and therapeutic effects of different types of exercise on youths. This network meta-analysis aimed to determine the best type of exercise type in the treatment and prevention of depression in youths. Methods: A comprehensive search of databases, including PubMed, EMBASE, The Cochrane Library, PsychINFO, Web of Science, and CNKI, was conducted to identify research on exercise intervention for depression in youth populations. The included studies were evaluated for risk of bias according to the Cochrane Handbook 5.1.0 Methodological Quality Evaluation Criteria. The network meta-analysis was performed using STATA 16.0. Result: Utilizing data extracted from 58 studies, we found that for depressed youth, exercise is significantly better than usual care in reducing anxiety. For non-depressed youth, exercise is significantly better than usual care in reducing anxiety. In the treatment of depression, resistance exercise (the surface under the cumulative ranking score, aerobic exercise, mixed exercise, and mind-body exercise showed significant efficacy over the control group using usual care. Resistance exercise, aerobic exercise, mind-body exercise, and mixed exercise were significantly effective in preventing depression compared to the control group using usual care. When evaluating the therapeutic and preventive effects of different types of exercise, we found that resistance exercise had the best effect on the treatment and prevention of depression in youths. Conclusion: This study demonstrates the positive association of exercise with depression and anxiety in youths and highlights the variability in the effectiveness of different types of exercise in treating and preventing depression in youths. Considering the treatment and prevention of depression in youths, resistance exercise should be recommended as the optimal type of exercise. In clinical practice, this finding has significant implications in the context of enormous implementation difficulties and the economic burden of treating and preventing depression in youths. However, more head-to-head studies are needed to confirm these findings.